IDENTIFYING THE CHARACTERISTICS AND DETERMINANTS OF SUCCESSFUL SOCIAL INNOVATIONS - Kulkarni, Arpit (2014)
In the light of its rising popularity across the globe, ‘social innovation’ is chosen as the phenomena for this MBA project dissertation. Social innovation could be defined as a novel solution to a social problem - a solution that is more effective and sustainable than the existing solutions and imparts benefits to the society as a whole. Though ‘social innovation’ is frequently confused with the terms ‘social entrepreneurship’ and ‘social enterprise’, it distinctly differs from the two, and imparts economic and social benefits to social actors such as governments, businesses, and the society.